1984
DOI: 10.1038/bjc.1984.178
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian carcinoma cells in culture: Assessment of drug sensitivity by clonogenic assay

Abstract: Cancer of the ovary is a major clinical problem and the most common cause of death from gynaecological malignancy in the United Kingdom. A particular feature is late presentation and the majority of patients present with advanced disease. Selection of effective first-line chemotherapy is therefore central to effective management.The development of in vitro assays for the growth of clonogenic tumour cells in soft agar (Hamburger & Salmon, 1977;Hamburger et al., 1978) suggested a system which might be of benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In the monolayer assay described here 39% of all tumours tested were very sensitive to CIS (<40% of control) and 71% showed some sensitivity (<60% of control). These values are very similar to those reported by Simmonds and McDonald (1984) for CIS sensitivity (48% sensitive, 79% intermediate + sensitive). Thus, in spite of their intrinsic differences the monolayer and clonogenic assays are predicting similar response rates of primary ovarian carcinoma cells to CIS.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the monolayer assay described here 39% of all tumours tested were very sensitive to CIS (<40% of control) and 71% showed some sensitivity (<60% of control). These values are very similar to those reported by Simmonds and McDonald (1984) for CIS sensitivity (48% sensitive, 79% intermediate + sensitive). Thus, in spite of their intrinsic differences the monolayer and clonogenic assays are predicting similar response rates of primary ovarian carcinoma cells to CIS.…”
Section: Discussionsupporting
confidence: 80%
“…that it can be used to show variations in the chemosensitivities of human ovarian tumours which reflect the clinically found pattern of response to chemotherapy. The overall success rate with the assay was -40% which is considerably lower than the 80% success rate which has been reported by groups using the clonogenic assay (Von Hoff et al, 1983;Simmonds & McDonald, 1984). However, the number of drug tests achieved for each successful monolayer culture exceeds that which is normally possible for the clonogenic assay.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Several investigators have reported that patients pretreated with DDP had low-level resistance to DDP, and that human ovarian carcinoma cell lines derived from the patients' tumor at the time the tumor became unresponsive to DDP were only two-to fourfold resistant to DDP (3)(4)(5)(6). In several in vivo murine models, DDP-resistant cell lines could be isolated from tumors treated with as few as two doses of DDP (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…Cells selected for resistance to many antimetabolites (1), and to drugs participating in the multiple drug resistance phenotype (2), often exhibit very high levels of resistance. In contrast, both in vitro and in vivo selection with DDP at clinically relevant intensities usually results in low-level resistant cells which are only two-to fourfold resistant to this drug (3)(4)(5)(6). Attempts to enhance the sensitivity to DDP have focused on strategies such as reduction of glutathione (7)(8)(9)(10) and inhibition of DNA repair ( 1,12).…”
Section: Introductionmentioning
confidence: 99%